Screen-based sedentary behaviors but not total sedentary time are associated with anxiety among college students - Huang, Tao; Zheng, Kefeng; Li, Shiyuan; Yang, Yanxiang; Kong, Lingxuan; Zhao, Ying (Frontiers in Public Health, 2022)
Objective: The purpose of the study was to investigate the associations of device-measured total sedentary time and screen-based sedentary time with anxiety in college students. Method: Three hundred and twenty-one college students (mean age = 19.72±1.18, 55.8% females) were recruited from Shanghai, China. Total sedentary time was objectively measured using accelerometry, while screen-based sedentary time was self-reported. Anxiety symptom was evaluated using the Self-Rating Anxiety Scale. Linear regression modelling was used to assess the associations of total sedentary time and screen-based sedentary time with anxiety symptoms. Results: Accelerometer-assessed total sedentary time was not associated with anxiety symptoms. Prolonged sedentary time on TV and movie viewing (>2 hours on weekdays) and social networking (>2 hours on weekdays and weekend) were associated with a higher level of anxiety. However, time on video gaming and recreational reading was not associated with anxiety symptoms. Conclusion: The findings indicated that screen-based sedentary behaviors but not total sedentary time were associated with anxiety symptoms among college students. The associations of screen-based sedentary behaviors with anxiety symptoms varied by the types of screen time.